2020
DOI: 10.15446/dyna.v87n214.83722
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the partial replacement of wheat flour with turmeric flour (Curcuma longa) on the physicochemical and sensory properties of a common chorizo

Abstract: The effect of partial replacement of wheat flour with turmeric flour (Curcuma longa) on the physicochemical and sensory properties of chorizo made with pork was evaluated. Three levels of turmeric flour substitution were proposed 0.8%, 1.4% and 2.1%, corresponding to a substitution of a 19.04%, 33.33% and 50,00%, respectively, along with a control chorizo without the addition of said flour. The pH, water holding capacity, color, texture and sensory evaluation were measured. The pH tended towards acidity in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 47 publications
(44 reference statements)
2
3
0
Order By: Relevance
“…These data agree with previous studies that reported a significant reduction of redness after the incorporation of Moringa seeds on beef burgers and green tea on hamburgers (Al-Juhaimi et al, 2016;Fachinello et al, 2018). Meanwhile, other authors demonstrated a slight reduction of redness after the incorporation of oregano essential oil into beef burgers (Leite et al, 2022), and turmeric powder into chorizo (Hleap-Zapata et al, 2020). The addition of turmeric also increased the yellowness (b*) of the fish patties, and this agreed with the study by Mancini et al (2015), who showed a significantly higher yellowness value in turmeric treated-rabbit burgers.…”
Section: Colour Propertiessupporting
confidence: 92%
See 1 more Smart Citation
“…These data agree with previous studies that reported a significant reduction of redness after the incorporation of Moringa seeds on beef burgers and green tea on hamburgers (Al-Juhaimi et al, 2016;Fachinello et al, 2018). Meanwhile, other authors demonstrated a slight reduction of redness after the incorporation of oregano essential oil into beef burgers (Leite et al, 2022), and turmeric powder into chorizo (Hleap-Zapata et al, 2020). The addition of turmeric also increased the yellowness (b*) of the fish patties, and this agreed with the study by Mancini et al (2015), who showed a significantly higher yellowness value in turmeric treated-rabbit burgers.…”
Section: Colour Propertiessupporting
confidence: 92%
“…It has been demonstrated that the addition of cloves and turmeric increased the lightness (L*) of the fish patties. Similar observations were also reported by Augustyńska-Prejsnar et al (2021) and Hleap-Zapata et al (2020), who demonstrated the increased lightness of the cooked duck burgers incorporated with turmeric extract and paste, and chorizo incorporated with turmeric powder, respectively. However, it has been reported the reduction in lightness of the raw beef burgers after being treated with 2% of clove powder (Ahmed et al, 2022), while no effects of raw and cooked beef patties after being treated with 0.1% of clove extract (Zahid et al, 2019;Zahid et al, 2020;).…”
Section: Colour Propertiessupporting
confidence: 89%
“…Similar results were obtained by Júnior et al [18] using the addition of curcumin microcrystals to a mortadella sausage. Additionally, studies by Hleap-Zapata et al [40] showed that the addition of turmeric in the form of powder increased the brightness of chorizo sausage. The authors' research showed that the storage time had an effect (p ≤ 0.001) on the brightening of the colour of all tested burgers (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…Júnior et al [18] showed that the addition of microcrystalline turmeric reduced the colour acceptance of mortadella, but had no effect on other sensory attributes. Hleap-Zapata et al [40] noted that the addition of turmeric powder to chorizo sausages in the amount of 2.1% did not lower the colour acceptability scores, but had a negative effect on the taste due to their acidification. In the studies of Febrianta et al [21], it was shown that marinating chicken breast muscles in 7.5% microencapsulated turmeric extract had a beneficial effect on the sensory characteristics of the refrigerated product, including taste attractiveness.…”
Section: Resultsmentioning
confidence: 99%
“…A cured raw sausage of Spanish origin, its preparation has spread throughout the world; its formulation and preparation vary according to country and even region [10,11]. According to Colombian Technical Standard NTC 1325, chorizo is a fresh, raw, and processed meat product obtained by grinding or mincing cooked and matured meat, together with fat and other permitted substances [12]. Vacuum frying is a technological alternative that improves the conditions of the frying process, while maintaining the sensory properties and product quality [13].…”
Section: Introductionmentioning
confidence: 99%